Igniting the Spirit of the Personal Data Protection Law: Advancing Justice, Ethics, and Institutional Reform in Indonesia’s Digital Legal Politics - Hamonangan, Marcellius Kirana; Silalahi, Wilma (Journal of Business, Management, and Social Studies, 2025)
This study investigates the legal and institutional challenges in implementing Law Number 27 of 2022 on Personal Data Protection (PDP Law) in Indonesia, with a particular focus on its capacity to uphold justice, ethical governance, and technological accountability in the digital age. This study employs a juridical-empirical approach through a comprehensive literature-based analysis. It integrates classical legal theories such as the Rechtsstaat principle and Gustav Radbruch’s Trichotomy of Law, alongside modern frameworks, including Responsive Law, Living Law, the concept of the Digital Panopticon, and Behavioral Law. This study reveals that the current PDP Law suffers from several deficiencies, notably the absence of an independent supervisory authority, the lack of explicit mechanisms for algorithmic oversight and the right to explanation, and inadequate remedies for data breach victims. These issues hinder the law’s effectiveness in confronting the complexities of digital society. This study introduces a cross-generational theoretical framework that connects foundational legal principles with contemporary digital realities. It offers a normative and institutional pathway to reform Indonesia’s data protection regime towards a more just, ethical, and human-centered legal order.